Peran Manajemen Sumber Daya Manusia Dalam Membangun Budaya Inovasi Di Lembaga Pendidikan - Sabari, Muhammad Hasbi; Cahyani, Dewi; Ali, Moh (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE ROLE OF HUMAN RESOURCE MANAGEMENT IN BUILDING A CULTURE OF INNOVATION IN EDUCATIONAL INSTITUTIONS The rapid development of global technology has brought significant changes in various aspects of life, including in the field of education. The purpose of this article is to identify HR management practices, explain how to lead, the organizational climate, and provide strategic recommendations for educational institutions. This research uses a qualitative-descriptive approach, while the data collection technique uses literature studies by collecting, and interpreting various written sources such as scientific journals, research articles, textbooks, policy documents, and reports of educational institutions. The results of this study show that the implementation of strategic, adaptive, and integrated human resource management is the main factor in fostering a culture of innovation in educational institutions. Practices such as competency-based recruitment, continuous professional development, proportionate reward systems, innovative leadership, and digital transformation play a significant role in building a creative, continuous learning-oriented work environment. In addition, visionary leadership, an open organizational climate, and strong institutional support have proven to strengthen the effectiveness of HR management in driving sustainable innovation.